M&A of assets: proposals to encourage their greater use - Hernández Gazzo, Juan Luis (2023)
The M&A of assets is a figure that presents certain particularities with respect to other mechanisms for the acquisition of businesses or companies (especially with respect to the purchase and sale of shares), such as (i) the possibility of choosing the assets -and liabilities- to be acquired; (ii) a due diligence process limited to the company or business being purchased (and not to the entire transferring company); (iii) a limited valuation process; (iv) a regime of representations and warranties focused mainly on the company or business acquired; and (v) full identification of the owner of the company or business in progress.In Peru there are several legal problems that make the M&A of assets a less efficient and more costly transaction. In this context, we propose a special regulation on the M&A of assets in Peru, to encourage its greater use.